Sweet Taste Receptors Mediated ROS-NLRP3 Inflammasome Signaling Activation: Implications for Diabetic Nephropathy - Luping Zhou; Wei Huang; Youhua Xu; Chenlin Gao; Ting Zhang; Man Guo; Yan Liu; Jingya Ding; Ludan Qin; Zihao Xu; Yang Long; Yong Xu (Journal of Diabetes Research)
Previous studies demonstrated that ROS-NLRP3 inflammasome signaling activation was involved in the pathogenesis of diabetic nephropathy (DN). Recent research has shown that sweet taste receptors (STRs) are important sentinels of innate immunity. Whether high glucose primes ROS-NLRP3 inflammasome signaling via STRs is unclear. In this study, diabetic mouse model was induced by streptozotocin (STZ) in vivo; mouse glomerular mesangial cells (GMCs) and human proximal tubular cells were stimulated by high glucose (10, 20, and 30 mmol/L) in vitro; STR inhibitor lactisole was used as an intervention reagent to evaluate the role and mechanism of the STRs in the pathogenesis of DN. Our results showed that the expression of STRs and associated signaling components (Gα-gustducin, PLCβ2, and TRPM5) was obviously downregulated under the condition of diabetes in vivo and in vitro. Furthermore, lactisole significantly mitigated the production of intracellular ROS and reversed the high glucose-induced decrease of Ca2+ and the activation of NLRP3 inflammasome signaling in vitro (p<0.05). These combined results support the hypothesis that STRs could be involved in the activation of ROS-NLRP3 inflammasome signaling in the pathogenesis of DN, suggesting that STRs may act as new therapeutic targets of DN.